Calculation of Safety Setback (Rs) For High Pressure Natural Gas Pipeline (Hazard Distances) - Abdallah I. Al Ejail; Abdunaser O. Susi; Nasseradeen M. Ashwear; Mahmud A. Eljaarani (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aims to analyze the required safety setback distance around high-pressure natural gas pipelines and assess the associated hazards. These pipelines run through Misurata City, supplying natural gas to the iron and steel company. The research focuses on essential safety regulations that companies must adhere to, considering the influence of pipeline diameter and internal operating pressure. Additionally, the study examines the role of safety valves in reducing internal pressure and mitigating potential risks. It defines critical safety distances, indicating that exceeding a specific radius (Rs) ensures safety, whereas certain hazardous zones require restricted access, with firefighters supported by water pumps for emergency response. Based on the findings, the study recommends increasing the minimum safety setback from 100 meters to 370 meters and raising public awareness about the potential dangers for residents living near these gas pipelines.